2023
DOI: 10.1007/s10695-023-01183-8
|View full text |Cite
|
Sign up to set email alerts
|

Elevated concentrations of organic and inorganic forms of iron in plant-based diets for channel catfish prevent anemia but damage liver and intestine, respectively, without impacting growth performance

Abstract: We compared the effects of using inorganic and organic forms of iron in plant-based diets on cat sh performance in a feeding trial with cat sh ngerlings (initial weight = 6.1 ± 0.2 g). Five diets supplemented with 0 (basal), 125, 250 mg Fe/kg of either FeSO 4 or iron methionine were formulated. Fish weight gain, feed conversion ratio, hepatosomatic index, and survival were similar among diets. Fish plasma and intestine iron concentration was similar among diets. Fish whole-body total lipid, protein, and dry ma… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
2

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 48 publications
2
2
2
Order By: Relevance
“…In contrast to the present study, alterations in intestinal architecture and histological scores were previously documented in channel catfish fed diets supplemented with iron, whether in the form of ferrous sulphate or methionine chelates (Buyinza et al, 2023). In addition, also contrasting with the present study, it has been observed necrosis, inflammation, lipidosis, and hyperemia on the hepatic histology in channel catfish and goldfish fed iron supplemented diets (Akbary & Jahanbakhshi, 2019;Buyinza et al, 2023).…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…In contrast to the present study, alterations in intestinal architecture and histological scores were previously documented in channel catfish fed diets supplemented with iron, whether in the form of ferrous sulphate or methionine chelates (Buyinza et al, 2023). In addition, also contrasting with the present study, it has been observed necrosis, inflammation, lipidosis, and hyperemia on the hepatic histology in channel catfish and goldfish fed iron supplemented diets (Akbary & Jahanbakhshi, 2019;Buyinza et al, 2023).…”
Section: Discussioncontrasting
confidence: 99%
“…For teleost fish, it is postulated that dietary iron is likely either stored in the liver or utilized during erythropoiesis, as suggested previously (Bury et al, 2012). This hypothesis aligns with observations made in channel and yellow catfish (Pelteobagrus fulvidraco), where a linear increase in hepatic iron concentration was observed when fish were offered diets containing graded levels of iron supplementation (Buyinza et al, 2023;Luo et al, 2017).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations